Fusion expression of nanobodies specific for the insecticide fipronil on magnetosomes in Magnetospirillum gryphiswaldense MSR-1 - Sha Wu (Journal of Nanobiotechnology, 2021)
Abstract Background Magnetic nanoparticles such as magnetosomes modified with antibodies allow a high probability of their interaction with targets of interest. Magnetosomes biomineralized by magnetotactic bacteria are in homogeneous nanoscale size and have crystallographic structure, and high thermal and colloidal stability. Camelidae derived nanobodies (Nbs) are small in size, thermal stable, highly water soluble, easy to produce, and fusible with magnetosomes. We aimed to functionalize Nb-magnetosomes for the analysis of the insecticide fipronil. Results Three recombinant magnetotactic bacteria (CF, CF+ , and CFFF) biomineralizing magnetosomes with different abundance of Nbs displayed on the surface were constructed. Compared to magnetosomes from the wild type Magnetospirillum gryphiswaldense MSR-1, all of the Nb-magnetosomes biosynthesized by strains CF, CF+ , and CFFF showed a detectable level of binding capability to fipronil-horseradish peroxidase (H2-HRP), but none of them recognized free fipronil. The Nb-magnetosomes from CFFF were oxidized with H2O2 or a glutathione mixture consisting of reduced glutathione and oxidized glutathione in vitro and their binding affinity to H2-HRP was decreased, whereas that to free fipronil was enhanced. The magnetosomes treated with the glutathione mixture were employed to develop an enzyme-linked immunosorbent assay for the detection of fipronil in water samples, with average recoveries in a range of 78–101%. Conclusions The economical and environmental-friendly Nb-magnetosomes biomineralized by the bacterial strain MSR-1 can be potentially applied to nanobody-based immunoassays for the detection of fipronil or nanobody-based assays in general.